2016
DOI: 10.3892/mmr.2016.4762
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of phospholipase Cε attenuates N-butyl-N-(4-hydroxybutyl) nitrosamine-induced bladder tumorigenesis

Abstract: Bladder cancer frequently shows mutational activation of the oncogene Ras, which is associated with bladder carcinogenesis. However, the signaling pathway downstream of Ras remains to be fully elucidated. N-butyl-N-(4-hydroxybutyl) nitrosamine (BBN) is able to induce bladder cancer by driving the clonal expansion of initiated cells carrying the activated form of Ras. Phospholipase Cε (PLCε) is the main target of BBN, while the tumor promoting role of PLCε remains controversial. The present study examined the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Phospholipase Cε (PLCε) is a member of the phospholipase C family, which catalyzes polyphosphoinositol, such as phosphatidylinositol 4,5-diphosphate, and produces the second messenger, including 1,4,5-triphosphate and diacylglycerol (8). Our previous studies demonstrated that PLCε may serve an important role in UBC growth (9,10) and activation of the signal transducer and activator of transcription 3 (STAT3) pathway (11). STAT3 is involved in the development and progression of a variety of tumor types, including colon, gastric and liver cancer (1214), which may be partially achieved by regulating anaerobic glycolysis (15).…”
Section: Introductionmentioning
confidence: 99%
“…Phospholipase Cε (PLCε) is a member of the phospholipase C family, which catalyzes polyphosphoinositol, such as phosphatidylinositol 4,5-diphosphate, and produces the second messenger, including 1,4,5-triphosphate and diacylglycerol (8). Our previous studies demonstrated that PLCε may serve an important role in UBC growth (9,10) and activation of the signal transducer and activator of transcription 3 (STAT3) pathway (11). STAT3 is involved in the development and progression of a variety of tumor types, including colon, gastric and liver cancer (1214), which may be partially achieved by regulating anaerobic glycolysis (15).…”
Section: Introductionmentioning
confidence: 99%
“…The authors identified that SPARC restrains urothelial carcinogenesis, progression and metastasis through an effect on cancer cells inhibiting carcinogen-induced cell cycle deregulation and on stromal cell plasticity, inhibiting their acquisition of a pro-inflammatory cancer associated phenotype. In another study, utilizing Rgs6 −/− mice, the role for RGS6 as a tumor suppressor was reported as they displayed accelerated pathological lesions than Rgs6 +/+ mice [ 46 ]. The investigators identified RGS6 as a tumor suppressor modulating ATM/p53 and RASSF1A, the two critical signaling pathways that are often dysregulated in urothelial carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…BBN-induced rodent models were analyzed by genome-wide analysis of copy number aberrations in bladder lesions [ 47 ]. The tumor promoting effect of phospholipase Cε (PLCε) was also studied using BBN in PLCε knockout mice [ 46 ]. The tumor promoting effect of PLCε was demonstrated by a decreased incidence of ensuing urothelial lesions in PLCε knockout mice compared to their wildtypes as well as a significant downregulation of PLCε downstream targets such as VEGF-A and COX-2 [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations